Pemanfaatan Media Sosial Instagram @fuadiainponorogo sebagai Media Informasi Mahasiswa Fakultas Ushuluddin Adab dan Dakwah IAIN Ponorogo Angkatan 2020 - Purdiyaputri, Dewi Ayuni; Marwantika, Asna Istya (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
People have done various ways to get information to fulfil their information needs. Until the presence of social media that changes lifestyles, thinking patterns, social society, and education. The presence of Instagram social media is one of the contemporary social media that is of interest to various groups to access information including lectures. This research aims: (1) To describe the motives for using Instagram social media @fuadiainponorogo as information media for FUAD IAIN Ponorogo students class of 2020. (2) To analyse the fulfilment of information needs of FUAD IAIN Ponorogo students class of 2020 on Instagram social media @fuadiainponorogo as information media. The method used is a qualitative descriptive approach. Data analysis using Miles and Hubberman, namely data reduction, data presentation, data verification, and conclusion drawing. Research results: First, the motives for utilising social media Instagram @fuadiainponorogo as information media are four in the MAIN model, namely information arises because of the use of Instagram @fuadiainponorogo as the dissemination of lecture information. Entertainment is seen from posting video reels that follow the trend. Social interaction arises from the interaction between the Instagram account admin @fuadiainponorogo and followers. Personal identity because Instagram account followers @fuadiainponorogo average student Faculty of Ushuluddin, Adab and Da'wah. Second, fulfilling the need for information on the Instagram account @fuadiainponorogo is enough to meet the information needs of students of the Faculty of Ushuluddin, Adab and Da'wah class of 2020 as an information media that requires more lecture information posts.